Promoting Pro-Environmental Behaviors via Green HRM: The Roles of Green Empowerment and Leadership - José Moleiro Martins; Muhammad Umair Ahmed; Farah Samreen; Muhammad Farrukh Shahzad (Ital Publication, 2025)
With growing environmental concerns, organizations worldwide are increasingly integrating green practices into their operational frameworks. The interplay between GHRM practices, green empowerment, and green leadership creates a conducive environment for promoting task-related and broader proactive pro-environmental performance among employees. Effective GHRM practices lay the foundation, while green empowerment acts as the driving force, and green leadership enhances the overall impact, ensuring a sustainable organizational culture. Therefore, this study explores the influence of GHRM practices on task-related proactive pro-environmental performance (T-PEP) and proactive pro-environmental performance (P-PEP) through green empowerment. This study examines the moderating role of green leadership in GHRM and green empowerment. Using partial least squares structural equation modeling (PLS-SEM), we analyze data collected from 312 Pakistan food industry employees. The results indicate that GHRM significantly influences the P-PEP and T-PEP through green empowerment of employees’ food industries of Pakistan. Additionally, green leadership is identified as a significant moderator in the relationship between GHRM and green empowerment. These findings underscore the importance of aligning HRM practices with leadership initiatives to cultivate an organizational culture supportive of environmental sustainability. Based on affective events theory principles, this study offers theoretical insights and practical guidance, presenting valuable recommendations for industry managers and academic researchers in the food manufacturing sector.